EFFICACY OF BOERHAAVIA DIFFUSA L. ON DISRUPTION OF GONADOTROPINS AND TESTOSTERONE IN FLUORIDE INTOXICATED MALE RATS - A, Shashi; Khan, Imtiaza (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The present study explored the influence of fluoride exposure on gonadotropins and reproductive hormones. Methods: Male Wistar albino rats weighing 100-150 g were administered with 100, 200, and 300 ppm/kg body weight of sodium fluoride daily for 20 and 40 days. The control group was given 1 ml deionized water/kgbw/day for the same period. At the end of the experimental period, half of the animals were sacrificed and blood serum was collected and testis sample was taken concurrently. Remaining half rats were administrated with two doses (250 mg and 500 mg/kg body weight) of leaf extract of Boerhaavia diffusa L. for another 20 days. Serum level of follicle-stimulating hormone (FSH), luteinizing hormone (LH), testosterone, and intratesticular level of testosterone were evaluated. Results: It was found that fluoride intoxication resulted in significant increase in the level of FSH (p<0.01) and LH (p<0.0001) while significant decrease in the serum (p<0.01) and testis (p<0.0001) level of testosterone. A significant (p<0.0001) positive correlation was found between level of serum fluoride and gonadotropins: FSH (20 days, r=0.708 and 40 days, r=0.795) and LH (20 days, r=0.779 and 40 days, r=0.891). However, there was significant (p<0.0001) negative correlation existed between serum fluoride and testosterone levels in serum (20 days, r=âˆ’0.780 and 40 days, r=âˆ’0.862) as well as testis (20 days, r=âˆ’0.915 and 40 days, r=âˆ’0.938). Conclusion: It was found that administration of B. diffusa L. alleviated the adverse effects of fluoride on reproductive endocrine functions.